Soil loss reduction and rainwater management in climate smart maize and coffee production systems - Baumann, Jurgen; Silva, Mayesse Aparecida da; Moran, David; Cazún, Bayron; Keough, Adam (2022)
In 2021, Alliance Bioverity International and CIAT (ABC) together with Catholic Relief Services (CRS) and Raindrop established an erosion-measuring project in maize and coffee in the department of Ahuachapan, El Salvador. Runoff and soil loss were measured in Wishmeier erosion plots. Each site had three plots, one control plot with bare soil and two with vegetation. One of the latter with additional soil conservation measures. Single high erosive rainfall events in the period just before and after sowing maize can lead to extreme soil losses on an unprotected soil surface. In the maize cropping system mulching in combination with Canavalia cover crop reduced soil loss and runoff in an effective way. The two soil types have shown a remarkable difference in their resistance to erosive rainfall impact. The Andosol soil with dense shaded coffee and ground cover vegetation provides a resilient land management system that buffers the impact of high rainfall, offering important hydrological services.